1970
DOI: 10.3126/sw.v9i9.5518
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> seed germination and seedling development of <i>Phaius tancarvilleae</i> (L’Her.) Blume.

Abstract: Abstract:In vitro seed germination and seedling development of Phaius tancarvilleae (L'Her.) Blume. was carried out on 0.8%(w/v) agar solidified MS Medium (Murashige and Skoog, 1962) without hormones or supplemented with different concentration and combination of Naphthalene acetic acid (NAA) and 6-benzylaminopurine (BAP). MS medium supplemented with 0.5 mg/l of BAP was the most ideal condition for early seed germination, protocorm formation and development of seedlings. Germination started after 7 weeks of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 3 publications
6
11
0
Order By: Relevance
“…During the last 50 years, tissue culture techniques using different explants have been extensively exploited, not only for the rapid and large-scale propagation of orchids but also for their ex situ conservation. Different protocols have been developed for the large-scale propagation of a number of orchid species and hybrids through in vitro culture of various parts including shoot tips, flower stalk, nodes, buds, stems, root tips and rhizome segments (Vij, 1993;Nayak , 1998;Kanjilal et al, 1999;Chang and Chang, 2000b;Chen et al, 2003b;Chugh et al, 2009;Pant and Shrestha, 2011;Deb and Pongener, 2012;Paudel and Pant, 2012). Mass propagation of medicinal orchids using in vitro culture technique has been reported by some workers (Sharma and Chandel, 1996;Liu and Zhang, 1998); Nalawade et al, 2003;Shiau et al, 2005;Basker and Bai 2006;Sharma et al, 2007;Pant et al, 2008;Hossain et al, 2009Hossain et al, , 2012Kaur andBhutani, 2009, 2010;Nongdam and Chongtham, 2011;Pant and Thapa, 2012;Pradhan et al, 2013).…”
Section: Propagation Of Orchids Using Different Explantsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 50 years, tissue culture techniques using different explants have been extensively exploited, not only for the rapid and large-scale propagation of orchids but also for their ex situ conservation. Different protocols have been developed for the large-scale propagation of a number of orchid species and hybrids through in vitro culture of various parts including shoot tips, flower stalk, nodes, buds, stems, root tips and rhizome segments (Vij, 1993;Nayak , 1998;Kanjilal et al, 1999;Chang and Chang, 2000b;Chen et al, 2003b;Chugh et al, 2009;Pant and Shrestha, 2011;Deb and Pongener, 2012;Paudel and Pant, 2012). Mass propagation of medicinal orchids using in vitro culture technique has been reported by some workers (Sharma and Chandel, 1996;Liu and Zhang, 1998); Nalawade et al, 2003;Shiau et al, 2005;Basker and Bai 2006;Sharma et al, 2007;Pant et al, 2008;Hossain et al, 2009Hossain et al, , 2012Kaur andBhutani, 2009, 2010;Nongdam and Chongtham, 2011;Pant and Thapa, 2012;Pradhan et al, 2013).…”
Section: Propagation Of Orchids Using Different Explantsmentioning
confidence: 99%
“…Some media are designed for specific genera, while others for a broad spectrum. Plant growth regulators such as auxins and cytokinins are added in the media to enhance the seed germination in some orchids (Pant and Gurung, 2005;Stewart and Kane, 2006;Deb and Temjensangba, 2006;Johnson et al, 2007;Hossain, 2008;Pradhan and Pant, 2009;Pant et al, 2011). A large number of complex additives like coconut water, banana pulp, peptone, tomato juice, salep, honey and beef extract have been used in different media to show their effect on orchid seed germination (Mitra, 1971;Vij, 1993;Hua and Zhiguo, 1998;Mohammad et al, 2009).…”
Section: Different Media Used For Orchid Culturementioning
confidence: 99%
“…could not undergo further differentiation in hormone free MS medium because terrestrial orchids require more regulated conditions of hormones for immature seeds to develop into seedlings (Pant et al, 2011). The results from the above findings showed that hormone supplemented MS basal medium were found more effective for further growth and development of the seedlings.…”
Section: Seedsmentioning
confidence: 88%
“…This problem can be overcome by tissue culture technique (Pradhan et al, 2013). In vitro asymbiotic germination is possible only by tissue culture method because it substitutes the action of fungus with a nutrient medium (Pant et al, 2011). Rapid in vitro germination of seeds and development take place in the controlled environment and requires no competition with fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of a reliable cloning methodology for P. tancarvilleae is important in terms of enabling the rapid propagation and production of a large number of high quality plants. We have already reported the in vitro propagation of P. tancarvilleae by immature seed culture (Pant et al 2011). The present investigation is undertaken to develop an efficient protocol for in vitro micropropagation of this commercially threatened species through shoot tip culture and to introduce this species in natural habitat.…”
Section: Introductionmentioning
confidence: 99%